Extramedullary Relapse in RARA Rearrangement-negative Acute Promyelocytic Leukemia Successfully Treated in Combination With Chemotherapy, Local Radiotherapy, and Cord Blood Transplantation. Issue 4 (May 2015) - Igarashi, Keita; Hori, Tsukasa; Yamamoto, Masaki; Inazawa, Natsuko; Noguchi, Hiroko; Suzuki, Nobuhiro; Somekawa, Yukihiro; Sasaki, Mayumi; Tsutsumi, Hiroyuki; Hatakeyama, Naoki
Abstract : RARA rearrangement-negative acute promyelocytic leukemia (APL) is uncommon, and its extramedullary relapse is extremely rare. We report a 5-year-old girl with RARA rearrangement-negative APL, which recurred solely at the external auditory canal and mastoid air cells. She was successfully treated with chemotherapy, local radiotherapy, and unrelated cord blood transplantation. She has maintained complete remission for 24 months after transplantation. The clinical features and our therapeutic strategy in this patient will provide valuable information for extramedullary relapse of RARA rearrangement-negative APL.